Sistem Informasi Akuntansi Pencatatan dan Pengelolaan Keuangan pada Kantor Sinode GPIBK Berbasis Web - Makidong, Sefriyawan; Frida Unsong, Imelda; Pola, Riski (Pusat Riset dan Inovasi Nasional, 2025)
The development of information technology has driven a significant transformation in accounting data management, especially in educational institutions, companies, and non-profit organizations. Web-based accounting information systems are a strategic solution to improve accuracy, transparency, and efficiency in financial management. This research aims to design and implement a web-based accounting information system that is able to support the management of the cash receipt and expenditure cycle, the preparation of financial statements, and the strengthening of internal controls. The method used is applied research with a case study approach in organizations that require real-time and integrated recording of financial transactions. The system development process includes needs analysis, system design, implementation, and testing. The results of the study show that the system built provides transaction recording features, account grouping according to accounting standards, and automatic presentation of financial statements. The system also supports internal audits through structured data storage and user rights-based access. In addition, the system has been proven to improve the effectiveness of internal controls, reduce the risk of human error, and speed up the presentation of information to management. The implications of this study suggest that small and medium-sized organizations can leverage these systems to improve transparency, accountability, and quality of financial decision-making. Thus, the implementation of a web-based accounting information system has the potential to support more professional, efficient, and sustainable financial governance.